Incidence and Risk Factors of Postoperative Nausea and Vomiting after General Anesthesia for Elective Surgeries - Hashim, Dr. Sattar Jaber (Academic Journal of Clinicians, 2024)
Postoperative nausea and vomiting (PONV) are common and bothersome side effect after general anesthesia; many patients rank it as the worst experience together with postoperative pain and intraoperative awakening. PONV increase the risk of postoperative complications, delay discharge from the post anesthesia care unit (PACU), and represent one of the leading causes of unplanned hospital admission after surgery, contributing to increased hospital costs. We aimed to assess the incidence and risk factors associated with the occurrence of PONV in patients undergoing general anesthesia for elective surgeries. Hence, during a period of 12 months we included a convenient sample of 123 consequent Iraqi patients at AlSader Teaching Hospital who were undergoing elective surgeries under general anesthesia.and assessed them postoperatively for the incidence of PONV. We used Apfel scoring system to evaluate the risk scores and estimated the number of risk factors. We found that 25 patients developed PONV contributed for 20.3% of the studied group.In conclusion, The incidence of PONV in general anesthesia for elective surgery was 20.3%; comparable to other studies and it. The patient’s own risk factors that were identified were being female, non-smoking, and having a history of motion sickness or PONV and those related to the anesthetic procedure, those related to the surgical act, were the surgical intervention with a conventional approach, the non-ambulatory approach and a surgical time greater than one hour. The increase in the number of determining factors in risk estimation was associated with its increase.